Rethinking Multiculturalism in an Era of Blurred Cultural Boundaries - Sabar Aritonang Rajagukguk; Saraswati Putri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper departs from the phenomenon of the dominance of patriarchal families in the large Batak family community which finally extinguishes the instinct of a mother to her child. Mother feels fine not to meet and not give affection or get affection from her child. The reason is absolute: her extended family doesn't want her, because the child does a different will from what the extended family expects. The exclusion or exile of those who are different has long been studied in the topic of multiculturalism. However, research on multiculturalism so far is still focused on how to facilitate cultural diversity or community groups. That is why there is a research gap showing that multiculturalism is becoming less relevant in capturing reality; because in group dynamics, individuals in one cultural group are not necessarily facilitated. It is the dominant individual who forms the identity of the group; so, there is a neglect of other individuals in the group. This paper aims to fill this research gap. Using Emmanuel Levinas’ ideas from Totality and Infinity, this research proposes a thesis that, given the difficulty of defining cultural boundaries in an age of interconnectedness, multiculturalism actually goes beyond recognition of cultural or group differences within community groups.